2018
DOI: 10.1007/s11548-018-1742-6
|View full text |Cite
|
Sign up to set email alerts
|

Prostate segmentation in transrectal ultrasound using magnetic resonance imaging priors

Abstract: Our results suggest that utilizing MRI priors in TRUS prostate segmentation could potentially improve the performance at base and apex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Zhu et al involved a deep supervision strategy into CNN for prostate segmentation . Zeng et al utilized magnetic resonance imaging priors for TRUS prostate segmentation …”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al involved a deep supervision strategy into CNN for prostate segmentation . Zeng et al utilized magnetic resonance imaging priors for TRUS prostate segmentation …”
Section: Introductionmentioning
confidence: 99%
“…Manual segmentation of the prostate on TRUS imaging is time-consuming and often not reproducible. For these reasons, several studies have applied deep learning to automatically segment the prostate using TRUS imaging [25][26][27][28][29][30][31].…”
Section: Challenges Applying Deep Learning To Abdominal Us Imagingmentioning
confidence: 99%
“…CNNs have outperformed other existing methods in the domain of sequence-based problems. CNNs were successfully applied to model sequence specificity of protein binding [15,16]. A convolutional three-layer network of CNN models was developed to predict the effects of noncoding variants of TF binding, DNA accessibility and histone marks of sequences from the only genomic sequence.…”
Section: Convolutional Neural Networkmentioning
confidence: 99%
“…A convolutional three-layer network of CNN models was developed to predict the effects of noncoding variants of TF binding, DNA accessibility and histone marks of sequences from the only genomic sequence. Research has shown that CNN has surpassed other existing methods [15], so developing structures that are not appropriate would yield a poorer result than convolutional models. The ability to match a CNN architecture to a given task lies in harnessing the power of CNNs.…”
Section: Convolutional Neural Networkmentioning
confidence: 99%